Structure and optical properties of GST - Almasov, N.Zh.; Dusembayev, S.A.; Tolepov, Zh.K.; Ussenbay, S.K.; Kadirov, A.I.; Keikimanova, M.T. (Recent Contributions to Physics, 2017)
The work presents the results of studies of structure and optical properties of nanoscale films with thickness from 50 to 175 nm of the GST system of the Ge2Sb2Te5 composition. The films were obtained on substrates using ion-plasma magnetron sputtering of a polycrystalline Ge2Sb2Te5 target in argon atmospheres at a pressure of 1 Pa and a sedimentation rate of 0.3 nm / s. Morphology and composition of films controlled by the method of scanning electron microscopy and energy-dispersion analysis. It is established that, in accordance with the illegal treatment against the abuse of alcohol and drugs. The structure of the films was studied by high-resolution transmission electron microscopy. It was found that the films are continuous and have a typical amorphous structure with short-range order. Spectral dependences of the absorption coefficients are calculated from the spectra of optical transmission and reflection of light of the films. It is established that for the nanosized Ge2Sb2Te5 films in the fundamental absorption region the quadratic Tautz law is satisfied. It is shown that the optical width of the band gap of films depends substantially on their thickness. With a decrease in the thickness of the films from 175 to 50 nm, their optical width of the forbidden band increases significantly from 0.63 to 0.96 times.